2015
DOI: 10.18293/dms2015-031
|View full text |Cite
|
Sign up to set email alerts
|

BopoNoto: An Intelligent Sketch Education Application for Learning Zhuyin Phonetic Script

Abstract: Abstract-The zhuyin phonetic script not only provides greater learning benefits compared to romanization systems for Chinese Mandarin language students with existing English fluency, but also allows students to take advantage of its use in Taiwan where it exists in both official and popular usage. However, while penenabled computing educational applications can assist traditional pedagogical approaches for accelerating mastery of the script, existing approaches are either constrained in providing writing asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…SE and AI fields were joined in one category. The majority of the studies (58% or 123 studies) included aspects of both observed disciplines, i.e., proposed an IUI solution with an accompanying algorithm along with the user interface for the proposed solution [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…SE and AI fields were joined in one category. The majority of the studies (58% or 123 studies) included aspects of both observed disciplines, i.e., proposed an IUI solution with an accompanying algorithm along with the user interface for the proposed solution [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of intelligent tutoring systems includes the integrated form of AI, so the spread of ITS in time will further disseminate these systems that are being used in education. These systems are used for adaptive feedback [23][24][25][26][27][28], presenting and recommending content [24,27,29,30].…”
Section: Ai In Educationmentioning
confidence: 99%